Changes of glycan expression in trophoblast cells: Possible biomarkers of cellular invasion (2023)
To characterize the glycosylation patterns of glycoproteins obtained from the choriocarcinoma cell line JEG-3 and the extravillous trophoblast cell line HTR8/Svneo stimulated with a hypoxiamimetic agent (CoCl2).